Geochemical Characteristics of Hydrothermal Volatiles From Southeast China and Their Implications on the Tectonic Structure Controlling Heat Convection - Tian, Jiao; Li, Yiman; Zhou, Xiaocheng; Pang, Zhonghe; Li, Liwu; Xing, Lantian; Li, Zhongping (Frontiers in Earth Science, 2021)
Hot springs and igneous rocks are present widely in southeast China, influenced by the subduction of the Western Pacific and Philippine Sea Plates. This study reports on new data of chemical compositions and He–Ne–C isotopes for gas samples from representative hot springs and wells in the Guangdong and Fujian provinces to identify the origin of hydrothermal volatiles and provide insight into geothermal tectonic affinities. The primary hydrothermal volatile component from southeast China is atmospheric N2, with a volumetric percentage of 82.19%–98.29%. It indicates medium-low temperature geothermal systems where geothermal fluids suffered a shallow circulation in closed fracture systems. Low CO2 and CH4 contents and their depleted δ13C values confirmed the small number of deep-derived components in the study area. However, spatially discernible geochemical characteristics imply enhanced hydrothermal fluid convection in the adjacent area of the two provinces, including the Fengshun, Zhangzhou, Longyan, and Sanming geothermal fields. Specifically, the He–Ne isotopes from this area exhibit mantle He contribution of more than 10% and mantle heat flow accounts for more than half of the total heat flow. Moreover, according to the thermal background calculations, the highest heat flow value of 77.7 mW/m2 is indicated for the Zhangzhou geothermal area and the lowest value of 54.7 mW/m2 is indicated for the Maoming geothermal area. Given the epicenter distributions and the corresponding earthquake magnitudes, the NE-trending faults are heat-control tectonic structures and their intersections with the NW-trending faults provided expedite channels for geothermal fluids rising to the surface. Therefore, the preferred development potential of geothermal resources can be expected in the adjacent area of the two provinces where two sets of active faults crossed. This study provides critical information on understanding the geothermal distribution controlled by the tectonic structure in southeast China.